Breast Feeding versus Formula Feeding and Diarrheal Diseases in Infants and Children- A Review - Begum, MUH (Journal of Bangladesh College of Physicians and Surgeons, 2014)
The World Health Organization (WHO) and the American Academy of Pediatrics (AAP) emphasize the value of breastfeeding for mothers as well as children. Both recommend exclusive breastfeeding for the first six months of life. Human breast milk is the healthiest form of milk for babies. Breastfeeding promotes health and helps to prevent diseases including diarrheal diseases. It contains all nutrients including antibodies (IgA),and lactoferrin, that potentially prevent infection and diarrhea in infants and children. Studies conducted in both developed and under developed nations have found that breast feeding is associated with significantly ( upto 64%) less diarrheal disease and the protective effect of breast feeding does not persist beyond two months after breast feeding is stopped. On the other hand, formula fed infants are found an upto 80% increased in the risk of developing diarrhea compared to breast fed infants and there is significantly more diarrheal disease in formula fed infants. Infection may be attributable to contamination of bottles, teats, milk, and food in infants who are not exclusively breastfed. Exclusive breastfeeding for the first six months of life and there after complementary feedings while breastfeeding continues for up to two years of age or beyond, enthusiastic support and involvement from clinicians, obstetricians and pediatricians, are essential in breastfeeding vs formula feeding issue and to reduce incidence of diarrheal diseases in infants and children. DOI: http://dx.doi.org/10.3329/jbcps.v32i1.21033 J Bangladesh Coll Phys Surg 2014; 32: 26-30